Nicotine Prevents Oxidative Stress-Induced Hippocampal Neuronal Injury Through α7-nAChR/Erk1/2 Signaling Pathway - Dong, Yun; Bi, Wenchuan; Zheng, Kai; Zhu, Enni; Wang, Shaoxiang; Xiong, Yiping; Chang, Junlei; Jiang, Jianbing; Liu, Bingfeng; Lu, Zhonghua; Cheng, Yongxian (Frontiers in Molecular Neuroscience, 2020)
Oxidative stress-induced neuronal damage has been implicated to play a dominant role in neurodegenerative disorders such as Alzheimer's disease (AD). Nicotine, a principal additive compound for tobacco users, has been demonstrated to attenuate amyloid-β-mediated neurotoxicity and NMDA-induced excitotoxicity. However, whether nicotine could protect neurons against oxidative injury remains largely unknown. In this study, the potential effects of nicotine on hydrogen peroxide (H2O2)-induced oxidative injury were investigated in a mouse hippocampal cell line (HT-22 cells). Here, we found that H2O2 resulted in cell cycle arrest at G2/M phase through excessive intracellular reactive oxygen species (ROS) generation and damaged mitochondrial functions. Importantly, nicotine at low concentrations significantly reduced intracellular ROS generation and increased cell proliferation against H2O2-induced oxidative injury. Besides, nicotine ameliorated mitochondrial dysfunction. Mechanistically, nicotine-mediated antioxidation were via specifically activating α7 nicotinic acetylcholine receptors (α7-nAChRs)/p-ERK1/2 signaling pathway rather than PI3K/Akt signaling pathway. Taken together, our findings provided an evidence for the neuroprotection of nicotine against oxidative injury, which indicates that nicotine may attenuate learning and memory injury by antioxidation in AD.